Advanced training in the Center of Excellence of healthcare and Pharmacy Specialists in 2018 - Center of Excellence of Healthcare; Pharmacy Specialists informs (Slauga. Mokslas ir praktika, 2020)
Sveikatos priežiūros ir farmacijos specialistų kompetencijų centro informacija apie tobulinimos galimybes 2018 metais.